La falta de afectividad por parte de los padres y/o representantes y su repercusión en el proceso enseñanza – aprendizaje de los niños y niñas de cuarto grado de educación general básica, de la escuela “Teniente Hugo Ortiz” de la parroquia El Valle, cantón y provincia de Loja, período lectivo 2013-2014 - Díaz Pucha, Carmen Rocío (2014)
In the present thesis entitled: “THE LACK OF EMOTION BY PARENTS AND / OR REPRESENTATIVES AND THEIR IMPACT ON LEARNING PROCESS - LEARNING CHILDREN OF FOURTH GRADE OF GENERAL BASIC EDUCATION, SCHOOL” LIEUTENANT HUGO. ORTIZ “the VALLEY PARISH, CANTON and Loja province, LECTIVO PERIOD 2013- 2014 “ was raised as a general objective: To contribute to the qualitative improvement of affective relations of parents and / or guardians of children of fourth grade of basic education School “Lieutenant Hugo Ortiz” Parish Valley Region and province of Loja, during the 2013-2014 school. The methodology used in the research process was based on the scientific, inductive, analytic and synthetic methods that allowed the sequential logical development of the proposed work; as the survey techniques is that girls and boys are applied, as well as teachers, parents School “Lieutenant Hugo Ortiz”. The main results are evidence that girls and boys are affected by the lack of affection from parents in the teaching- learning process. The respective sample is 35 girls and children from fourth grade eight teachers and 20 parents. The main conclusion reached is that parents prioritize their children’s economic welfare and education support, leaving the side how vital it is love, affection and understanding, which is fundamental bases stimulation and affection for the proper development of children, the main recommendation is aimed at parents cultivate dialogue with their children, when they make an act of indiscipline, and that minimize the use of corporal punishment, though many times necessary, if it is moderate and does not affect the physical and psychological integrity of children.